Análise da capacidade de pagamento versus a disposição a pagar pelo uso da água dos irrigantes do perímetro irrigado baixo Acaraú: Um estudo de caso - Jales, Juliana Viana (2009)
The objective of this study was to analyze the degree of sustainability of the Irrigated Perimeter Baixo Acaraú according to capacity to pay and willingness to pay of it irrigants. It was used secondary data and primary data from public institutions and the application of questionnaires and conduct of participative research. The methodology used for analysis of capacity to pay was through the removal of the socioeconomic characterístics of irrigant and the basic conceptual model called the “residual method”. For analysis of the efficient allocation of production factors built up to the prosuction function of Cobb-Douglas type. For analysis of the willingness to pay, questionnaires were applied. In relation to ability to pay, 21 irrigant (61,76%) proved to be without capacity to pay and three (8,82%) showed no willingness to pay. The production function showed a determination coefficient of 71%, showing that 71% of the variation in production can be explained by the variables included in the model. Despite the assumptions of the classical model have been tested and all have been met, the t statistic of the estimated coefficients were not significant, except for the inputs. The polynomial function having water as the only variable factor indicated that the majority of producers are using water to produce a rational way. The irrigant showed positive points of the Irriated Perimeter, with emphasis on the opportunity to have their own business and search for a better quality of life, while among the negative points of the perimeter, the most mentioned were acess to basic services, lack of organization producers and the lack of technical assistance. It is concluded that irrigation the Irrigated Perimeter Baixo Acaraú do not generally presented, capacity to pay. Despite the of perimeter infrastructure qualilty and the fact of irrigants to have willingness to pay for water they use, they don't have capacity to pay for water use, as they arre disorganized and do not reach good levels of production and marketing. Consequently, the perimeter does not show an acceptable level of sustainability. The disorganization of irrigants does not permit to establish strategies that lead to better performance of irrigants in the Irrigated Perimeter Baixo Acaraú.